Application of multi-pass high pressure homogenization under variable temperature regimes to induce autolysis of wine yeasts. (1st June 2017) - Comuzzo, Piergiorgio; Calligaris, Sonia; Iacumin, Lucilla; Ginaldi, Federica; Voce, Sabrina; Zironi, Roberto
Highlights: Number of passes and process temperature affect HPH-induced autolysis of wine yeasts. S. bayanus cells were inactivated in 10 passes without temperature control at 75 °C. Temperature control more effective than multi-pass for release of soluble molecules. Lower temperatures led to higher concentration of ethyl esters and aroma compounds. Different operating conditions allow to modulate the composition of the autolysates. Abstract: The effects of the number of passes and processing temperature management (controlled vs. uncontrolled) were investigated during high pressure homogenization-induced autolysis of Saccharomyces bayanus wine yeasts, treated at 150 MPa. Both variables were able to affect cell viability, and the release of soluble molecules (free amino acids, proteins and glucidic colloids), but the effect of temperature was more important. S. bayanus cells were completely inactivated in 10 passes without temperature control (corresponding to a processing temperature of 75 °C). The two processing variables also affected the volatile composition of the autolysates produced: higher temperatures led to a lower concentration of volatile compounds. The management of the operating conditions may allow the compositional characteristics of the products to be modulated, making them suitable for different winemaking applications.